2022
DOI: 10.5194/acp-22-13035-2022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ENSO-driven stratosphere-to-troposphere transport of ozone over North America

Abstract: Abstract. The El Niño–Southern Oscillation (ENSO) is known to modulate the strength and frequency of stratosphere-to-troposphere transport (STT) of ozone over the Pacific–North American region during late winter to early summer. Dynamical processes that have been proposed to account for this variability include variations in the amount of ozone in the lowermost stratosphere that is available for STT and tropospheric circulation-related variations in the frequency and geographic distribution of individual STT e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 82 publications
3
7
0
Order By: Relevance
“…The weakened polar vortex extended from the stratosphere to the troposphere (figures S2(e)-(h)), which is consistent with Baldwin and Dunkerton (2001). Previous studies have shown that geopotential height and ozone anomalies should be anticorrelated for medium-scale waves due to vertical motion and horizontal advection (Schoeberl andKrueger 1983, Salby andCallaghan 1993), which can further influence the stratosphere-to-troposphere transport (Albers et al 2022). Thus, the increase in ground-level ozone in North Eurasia and western North America may be related to the 2021 SSW of the vortex displacement type.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The weakened polar vortex extended from the stratosphere to the troposphere (figures S2(e)-(h)), which is consistent with Baldwin and Dunkerton (2001). Previous studies have shown that geopotential height and ozone anomalies should be anticorrelated for medium-scale waves due to vertical motion and horizontal advection (Schoeberl andKrueger 1983, Salby andCallaghan 1993), which can further influence the stratosphere-to-troposphere transport (Albers et al 2022). Thus, the increase in ground-level ozone in North Eurasia and western North America may be related to the 2021 SSW of the vortex displacement type.…”
Section: Resultssupporting
confidence: 81%
“…The model domain extends from the Earth's surface to the lower thermosphere (∼140 km or 5.96 × 10 −6 hPa). WACCM has been widely used in previous studies on the stratosphere-to-troposphere transport of ozone (Hess et al 2015, Yang et al 2016, Abalos et al 2020, Albers et al 2022.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a strong intraseasonal variability exists in the MD hotspot, with no events in August in this model simulation. Also, the interannual variability of the summer intrusion at the NA hotspot does not show a connection to ENSO (not shown), whereas the spring deep STT increases during La Ninas (Albers et al., 2022; Lin et al., 2015).…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Our study differs from previous works in that we identified hotspots of stratospheric intrusion with the frequency of extreme ozone events, which is directly relevant to the air quality. Most previous studies focus on a monthly or seasonal average amount of mass or ozone transported from the stratosphere to the troposphere (e.g., Albers et al., 2022; Škerlak et al., 2014; Sprenger & Wernli, 2003). Anomalously high amounts of ozone intrusion on a monthly scale are commonly associated with frequent extreme events.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation